Dietary raw starch to gelatinized starch ratios: Effects on the growth performance, digestive functions, intestinal histology and growth hormone‐insulin‐like growth factor‐I axis of blunt snout bream Megalobrama amblycephala. (13th December 2019) - Zhang, Li; Li, Xiangfei; Shi, Huajuan; Xu, Chao; Wang, Bingke; He, Chaofan; Zhang, Ling; Liu, Wenbin
Abstract: A 10‐week feeding trial was conducted to investigate the effects of dietary raw starch (RS)/gelatinized starch (GS) ratios on the growth, digestive functions, intestinal histology and the growth hormone‐insulin‐like growth factor‐I (GH‐IGF‐I) axis of Megalobrama amblycephala . Fish were randomly fed five diets containing various RS/GS ratios: 100/0, 75/25, 50/50, 25/75 and 0/100. Fish in the 75/25 group obtained the highest weight gain rate, specific growth rate, protein efficiency ratio and nitrogen retention efficiency compared with other groups, whereas the opposite was true for feed conversion ratio. Intestinal activities of amylase, maltase and sucrase all achieved the highest values in the 75/25 group. The highest lipase and α‐glucosidase activities were found in the 25/75 and 50/50 groups respectively. Activities of protease, alkaline phosphatase and Na +, K + ‐ATP decreased with the decreasing of RS/GS ratios. The villi length and crypt depth of the 75/25 group were significantly higher than that of the 100/0 group. Furthermore, the transcriptions of GH increased with the decreasing of RS/GS ratios with the highest observed in the 75/25 group. Overall, our findings indicated that a RS/GS ratio of 75/25 could benefit the growth performance of Megalobrama amblycephala by increasing intestinal digestive and absorptive capabilities as well as promoting GH release.